Protection of civilians in conflict Environment: Challenges and recommendations - Subramanian, Mohan (U.S.I. Journal)
In this era of increasing geopolitical multilateralism and questions being raised on the continued relevance of United Nations (UN) peacekeeping, one central fact remains indisputable. there is no better option available to the international community. The UN peacekeeping is as credible, politically neutral, and cost-effective as it gets for addressing global conflicts. given the enormous difficulties in achieving the ultimate political purposes of UN peacekeeping mission, 'Protection of Civilians' (POC) in the conflict-affected countries becomes the central and immediate purpose of UN peacekeeping missions While efforts to achieve political objectives continue. There are, however, several critical challenges that confront effective PoC actions by UN peacekeeping missions. They include non-unanimous 'Over Ambitious' mandates, 'Underresourcing' by member states, lack of genuine commitment by host government in supporting the UN peacekeeping missions, peacekeepers, and contingents that are not fully free from operational caveat, civilian, and military mindset issues, and an inability to adapt to emerging threats, amongst other challenges. The need of the hour is to confront these challenges, implement mitigating measures, and strengthen the faith that the world has in UN peacekeeping as the most credible, politically neutral, and effective instrument for addressing global conflicts, rather than 'Throwing the baby out with the bathwater'.
Keywords: Geopolitical multilateralism, United Nations(UN), UN peacekeeping missions